Acts and letters of the apostles - Bible. N.T. Acts. English. Lattimore. 1982; Lattimore, Richmond Alexander, 1906-1984 (New York, NY Farrar, 1982)
Includes notes.
Keywords: Bible. N.T. Acts -- English -- Lattimore -- 1982.; Bible. N.T. Epistles -- English -- Lattimore -- 1982.